4-(Methylsulfonyl)benzaldehyde - Qian, Shao-Song (International Union of Crystallography, 2009)
In the crystal of the title compound, C(8)H(8)O(3)S, the molecules are linked into a three-dimensional array by intermolecular C—H⋯O hydrogen bonds.